2011
DOI: 10.1186/1472-6963-11-243
|View full text |Cite
|
Sign up to set email alerts
|

Stages of change: A qualitative study on the implementation of a perinatal audit programme in South Africa

Abstract: BackgroundAudit and feedback is an established strategy for improving maternal, neonatal and child health. The Perinatal Problem Identification Programme (PPIP), implemented in South African public hospitals in the late 1990s, measures perinatal mortality rates and identifies avoidable factors associated with each death. The aim of this study was to elucidate the processes involved in the implementation and sustainability of this programme.MethodsClinicians' experiences of the implementation and maintenance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
148
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(160 citation statements)
references
References 26 publications
12
148
0
Order By: Relevance
“…Facility-based maternal death and surveillance review (MDSR) including maternal death reviews (MDRs), audits, and confidential enquiry of maternal death (CEMD) (at national level) usually supported by health managers at district, region/province, and national level, aim to identify avoidable factors and opportunities for improvement through a confidential multidisciplinary team discussion with contributions from staff involved in the patient's care and a review of the patient documentation (Beyond the Numbers, WHO 2004). [25] Belizán et al 2011 [26] Project-based maternal death reviews and audits support a district or facility to conduct the process for a period of time with external support.…”
Section: Typementioning
confidence: 99%
See 1 more Smart Citation
“…Facility-based maternal death and surveillance review (MDSR) including maternal death reviews (MDRs), audits, and confidential enquiry of maternal death (CEMD) (at national level) usually supported by health managers at district, region/province, and national level, aim to identify avoidable factors and opportunities for improvement through a confidential multidisciplinary team discussion with contributions from staff involved in the patient's care and a review of the patient documentation (Beyond the Numbers, WHO 2004). [25] Belizán et al 2011 [26] Project-based maternal death reviews and audits support a district or facility to conduct the process for a period of time with external support.…”
Section: Typementioning
confidence: 99%
“…• Government leadership and ownership strengthens accountability within the health sector and assures sustainability [24][25][26]. • Engagement of district hospitals improves organization and quality of care [27].…”
Section: Performance Accountabilitymentioning
confidence: 99%
“…Grol et al found that none of the popular models for improvement of care are superior and that different models should be integrated to achieve change [20]. Knowledge of the field in which a new technology needs to be implemented and awareness of the stages of change necessary to implement and sustain the implementation of the new technology is therefore an essential factor in the whole process [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, similar to the findings of Belizaán et al, the presence of the members of the project team at all the introductory audit meetings and their non-judgmental participation in subsequent meetings was greatly appreciated by the local caregivers and increased the acceptance of holding a perinatal audit. It also emphasized the importance of a unit-based perinatal audit in all groups and stimulated continuation of the audit meetings [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Understanding the causes of stillbirth allows services to develop to address specific populations' needs for preventing stillbirth. In many settings there have been substantial changes in perinatal and maternal mortality after the introduction of robust audits . Therefore, perinatal audit is essential at many different levels from individual maternity units up to national datasets.…”
Section: Determining the Causes Of Stillbirth And Perinatal Auditmentioning
confidence: 99%